Characterization of Mycoplasma Strains from Cats - Cole, B. C. (1967)
Mycoplasma strains (B1, B2, CS, and S1A) were isolated from the saliva of normal cats. These were compared with a strain (CO) isolated from the eye of a cat with severe conjunctivitis. On the basis of morphology, biochemical reactions, and antigenic composition, two distinct species were recognizable. Strains CO, B1, and B2 were antigenically unrelated to the other species tested; strains CS and S1A possessed antigenic components in common with Mycoplasma arthritidis, M. salivarium, M. hominis, type 1, and M. orale, types 1 and 2. It was tentatively suggested that the two cat species be called M. felis and M. gateae, respectively.